Morphological and Phylogenetic Studies of Three New Species of Calocybe (Agaricales, Basidiomycota) from China - Yue Qi; Aiguo Xu; Ye Zhou; Kexin Bi; Weiqiang Qin; Hongbo Guo; Xiaodan Yu (Diversity, 2022)
Three species, Calocybe lilacea, C. longisterigma, and C. subochraceus, were newly discovered in Inner Mongolia, Hunan, and Liaoning provinces of China. Calocybe lilacea is mainly characterized by its small-sized basidiocarp, brownish-orange pileus, lilac gray to dull violet stipe, and noncellular epicutis. The main characteristics of C. longisterigma are its light brown to brownish-orange pileus, long sterigmata, and noncellular epicutis. The main morphological features of C. subochraceus are its small-sized basidiocarp, pale-orange pileus, adnexed lamellae, tortuous stipe, and noncellular epicutis. These morphological features confirmed that the three species of Calocybe all belonged to Sect. Carneoviolaceae. Phylogenetic analysis based on a combined dataset (ITS–nrLSU–RPB2) determined that the three species belong to the genus Calocybe and form a distinct lineage. The morphological differences between the three new species and other related species of Calocybe are also discussed.